Depression and aphasia after stroke - Kontou, Eirini (2010)
Background: Post-stroke depression (PSD) is a common phenomenon and has a negative impact on rehabilitation, recovery and quality of life. About one third of stroke patients suffer communication problems, including aphasia, which is a condition that mainly affects their ability in understanding and/or producing language. The frequency of depressive symptoms in post-stroke aphasia has been difficult to determine as most studies have excluded stroke patients with aphasia due to methodological limitations. As a result, depression remains often under-diagnosed and untreated in these patients.